In vitro study on the effect of peucedanol on the activity of cytochrome P450 enzymes - Cun Zhang; Yongwei Li; Changlong Yin; Jie Zheng; Guozhi Liu (Taylor & Francis Group, 2021)
Context Peucedanol is a major extract of Peucedanum japonicum Thunb. (Apiaceae) roots, which is a commonly used herb in paediatrics. Its interaction with cytochrome P450 enzymes (CYP450s) would lead to adverse effects or even failure of therapy. Objective The interaction between peucedanol and CYP450s was investigated. Materials and methods Peucedanol (0, 2.5, 5, 10, 25, 50, and 100 μM) was incubated with eight human liver CYP isoforms (CYP1A2, 2A6, 3A4, 2C8, 2C9, 2C19, 2D6, and 2E1), in pooled human liver microsomes (HLMs) for 30 min with specific inhibitors as positive controls and untreated HLMs as negative controls. The enzyme kinetics and time-dependent study (0, 5, 10, 15, and 30 min) were performed to obtain corresponding parameters in vitro. Results Peucedanol significantly inhibited the activity of CYP1A2, 2D6, and 3A4 in a dose-dependent manner with IC50 values of 6.03, 13.57, and 7.58 μM, respectively. Peucedanol served as a non-competitive inhibitor of CYP3A4 with a Ki value of 4.07 μM and a competitive inhibitor of CYP1A2 and 2D6 with a Ki values of 3.39 and 6.77 μM, respectively. Moreover, the inhibition of CYP3A4 was time-dependent with the Ki/Kinact value of 5.44/0.046 min/μM. Discussion and conclusions In vitro inhibitory effect of peucedanol on the activity of CYP1A2, 2A6, and 3A4 was reported in this study. As these CYPs are involved in the metabolism of various drugs, these results implied potential drug-drug interactions between peucedanol and drugs metabolized by CYP1A2, 2D6, and 3A4, which needs further in vivo validation.